2013
DOI: 10.1039/c3cc46609d
|View full text |Cite
|
Sign up to set email alerts
|

Tunable color generation of transparent composite films reinforced with luminescent nanofillers

Abstract: A new composite film based on calcined layered rare earth hydroxides and poly(vinyl alcohol) shows a visible light transmittance comparable to that of the pure matrix, highly reinforced mechanical strength as well as tunable photoluminescence in rolled and folded shapes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Upon the addition of LRH dispersion to the mixed solution of SA and PAAS, the SA and PAAS chains were simultaneously and directly cross-linked with LRH forming SA/PAAS/LRH double physical cross-linked hydrogels, as shown schematically in Scheme . The abundant hydroxyl and oxygen-containing functional groups on surfaces endow LRH nanosheets with hydrophilic surfaces which are positively charged . This result was further confirmed by zeta potential measurement.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Upon the addition of LRH dispersion to the mixed solution of SA and PAAS, the SA and PAAS chains were simultaneously and directly cross-linked with LRH forming SA/PAAS/LRH double physical cross-linked hydrogels, as shown schematically in Scheme . The abundant hydroxyl and oxygen-containing functional groups on surfaces endow LRH nanosheets with hydrophilic surfaces which are positively charged . This result was further confirmed by zeta potential measurement.…”
Section: Resultssupporting
confidence: 57%
“…The abundant hydroxyl and oxygen-containing functional groups on surfaces endow LRH nanosheets with hydrophilic surfaces which are positively charged. 48 network structure contributes to enhancing the mechanical behavior of the hydrogel. 49 We found that the gelling ability of LRH and SA was stronger than that of LRH and PAAS through the frequency sweep (Figure S8).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Layered rare earth hydroxides (LRHs) with the general formula RE 2 (OH) 5 X•nH 2 O (RE = rare earths, X = organic and inorganic anions) are an emerging family of compounds with a wide range of potential applications including as catalysts, 13 multimodal imaging agents in cellular labeling for both fluorescent and magnetic resonance imaging, 14 multifunctional luminescent films, 15,16 selective bio- 17 and environmental 18,19 sensors for organic and inorganic anions, and luminescent nanofillers. 20 However, the inefficient direct 4f−4f excitation of rare earths, which is attributed to the parity and spin-forbidden transition, considerably limits practical application of LRHs in optical purposes. Furthermore, because water molecules and hydroxyl groups are included in the layer structure of LRHs, 21 vibrational modes of OH oscillators provide nonradiative decay pathways that effectively quench emissions from rare earth activators.…”
Section: Introductionmentioning
confidence: 99%
“…The interlayer anions are rarely used to modulate the emission colors. 34,35 We envisioned that since a layered structure of LRHs allows easy anion exchange, 36 by intercalation of anionic RE 3+ photosensitizers and blue-emitting chromophores, both RE 3+ luminescence (red and green) and blue color can be obtained, respectively, to further fabricate color-tunable or white-light emitting devices.…”
Section: Introductionmentioning
confidence: 99%